(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Functional endoscopic sinus surgery (FESS), effective control of bleeding is essential to maintain a clear operative field and to minimize complications. Intraoperative bleeding is one of the major problems in endoscopic surgery of sinuses. Controlled hypotension is a technique used to limit intraoperative blood loss to provide the best possible field for surgery. Objective: The objective of study was role of Hypotensive Anaesthesia in Functional Endoscopic Sinus Surgery and designed to compare intraoperative hemorrhage and the visibility of the operative field during normotension and hypotension anesthesia. Methods: Prospective randomized study includes a total of 60 ASA I-II patients who underwent elective FESS surgery. Patients randomly assigned in two groups the hypotension group (Group A) and the normotension group (Group B). Intraoperative mean arterial pressure (MAP), heart rate (HR) were recorded. Results : This study shows the mean ages of the patients of group A group B were 33.36±7.61 and 32.46±7.73 years respectively. No statistically significant difference was observed among groups at 0.05 level in term of age. The mean heart rate pre-anaesthesia and preoperative among the patients of different groups in different follows up period. Significance differences were observed among groups in term of heart rate at 5 minute, 15 minute, 30 minute, 45 minute and 60 minute. The mean arterial mean blood pressure before pre-anaesthesia and preoperative estimation among the patients of different groups in different follows up period. Significance differences were observed among groups at 5 minute, 15 minute, 30 minute, 45 minute and 60 minute. Conclusion: This study demonstrated that Controlled hypotension can be achieved equally and effectively by nitroglycerin and labetalol reduced significantly intraoperative hemorrhage and produce hypotensive anesthesia. Both are equally effective in providing ideal surgical field during functional endoscopic sinus surgery (FESS). Bangladesh J Otorhinolaryngol; April 2018; 24(1): 8-13